Comparison of clinicopathological patterns of renal tubular damage in dogs with acute kidney injury caused by leptospirosis and other aetiologies. (December 2020) - Zamagni, S.; Troìa, R.; Zaccheroni, F.; Monari, E.; Grisetti, C.; Perissinotto, L.; Balboni, A.; Dondi, F.
Highlights: Increased magnitude and frequency of glucosuria characterise leptospirosis in dogs. Renal wasting of potassium frequently occurs in canine leptospirosis. Urinary neutrophil gelatinase-associated lipocalin is similar in leptospirosis and other causes of acute kidney injury. Abstract: In humans, leptospiral acute kidney injury (AKI) is characterised by tubulointerstitial involvement and renal electrolyte losses, impacting clinical presentation and case management. The aim of this study was to evaluate urine chemistry findings in dogs with leptospirosis in order to identify characteristic patterns of tubular damage associated with this disease. Dogs with intrinsic AKI caused by leptospirosis and by other aetiologies were prospectively enrolled. Clinical and clinicopathological variables, including serum and urine chemistry, fractional excretion (FE%) of electrolytes, and urinary neutrophil gelatinase-associated lipocalin (NGAL), were evaluated in both groups and compared statistically. Dogs with leptospirosis ( n = 38) had significantly higher serum creatinine concentration than dogs with AKI caused by other aetiologies ( n = 37). Serum potassium and glucose concentrations were comparable between groups. Dogs with leptospiral AKI had significantly higher FE of potassium (median 100%, range 20–480 vs. median 68%, range 5–300; P = 0.048), as well as higher magnitude of glucosuria (urine glucose to creatinine ratio, median 0.64, range 0–26 vs. median 0.22, range 0–13; P = 0.023) and frequency of positive glucose dipstick reaction (59% vs. 18%; P = 0.002), than dogs with AKI of other aetiologies. Additional markers of tubular damage considered in this study, including FE of other electrolytes and urinary NGAL, did not differ between groups. In conclusion, when compared to other aetiologies of intrinsic AKI, canine leptospirosis was characterised by increased glucosuria and kaliuresis.